Behaviour of Steel-Soil Bridge Structure Made of Corrugated Plates Under Field Load Tests. Part I: Static Research - Zbigniew Mańko; Dariusz Bęben (Engineering Transactions, 2006)
The way in which a new road bridge made from Super Cor steel plates was tested is described and the test results, for three static load schemes in which one ballasting vehicle (a Scania truck) was used as the load, are presented. The tested bridge has a box structure and it is located on the Gimån River in Gimån, Sweden on the Bråcke – Holm road. The bridge has an effective span of 12.315 m and a clear height of 3.555 in. The steel shell of the span is founded on two reinforced concrete continuous foundations. The average measured displacements and unit strains (normal stresses) in selected points and elements of the steel shell structure were found to be much smaller than the ones calculated for the same load. The conclusions drawn from this research can be useful for assessing the behaviour of such steel shells and their interaction with the surrounding backfill. Since such steel–soil structures are used more and more often for small and medium-sized bridges on road arid railway lines in Poland and in the world, the conclusions from the static load tests can be generalized to a whole class of similar bridge structures.